Faktor Pendorong dan Faktor Penghambat dalam Penanggulangan Bencana Banjir di Kota Solok - Fairuz Fadhilah, Nabilah; Alhadi, Zikri (Policy, Law and Political Research Center, 2024)
This research focuses on the problem of flood disasters which often occur every year and flood management carried out by the Solok City government. The research was carried out with the aim of finding out the driving and inhibiting factors in flood management in Solok City. The research uses a qualitative approach with descriptive methods. The research locations are at the Regional Disaster Management Agency (BPBD) Solok City Office, Solok City Public Works and Spatial Planning Service (PUPR), and Solok City Housing and Settlement Area Service (PERKIM). Research informants used purposive sumpling techniques. Data collection was carried out by interviews, observation and document study and data analysis by data reduction, data presentation and drawing conclusions. The results of the research show that the government has made efforts to overcome floods by conducting outreach and simulations, carrying out monitoring, carrying out cleaning of river sediments and ensuring that river operations can run well. It requires encouragement from all parties so that it can be carried out well, but the implementation has not been effective because it is still ongoing. obstacles were found in its implementation.